2019
DOI: 10.2196/12641
|View full text |Cite
|
Sign up to set email alerts
|

Designing Robust N-of-1 Studies for Precision Medicine: Simulation Study and Design Recommendations

Abstract: Background Recent advances in molecular biology, sensors, and digital medicine have led to an explosion of products and services for high-resolution monitoring of individual health. The N-of-1 study has emerged as an important methodological tool for harnessing these new data sources, enabling researchers to compare the effectiveness of health interventions at the level of a single individual. Objective N-of-1 studies are susceptible to several design f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…More stratification of patients leads to increasingly small patient (sub)groups, complicating the generation of (sufficiently) statistically powered data on treatment effectiveness through traditional randomised controlled trials (RCTs). Several alternative trial designs have been developed, including basket trials [ 31 , 32 ], umbrella trials [ 31 ], n-of-1 trials [ 33 ] and adaptive trials [ 34 ]. While some of these alternative designs still allow for controlled studies, many are single-arm designs.…”
Section: Resultsmentioning
confidence: 99%
“…More stratification of patients leads to increasingly small patient (sub)groups, complicating the generation of (sufficiently) statistically powered data on treatment effectiveness through traditional randomised controlled trials (RCTs). Several alternative trial designs have been developed, including basket trials [ 31 , 32 ], umbrella trials [ 31 ], n-of-1 trials [ 33 ] and adaptive trials [ 34 ]. While some of these alternative designs still allow for controlled studies, many are single-arm designs.…”
Section: Resultsmentioning
confidence: 99%
“…Such models may not be applicable to all N-of-1 studies. It would be of value to assess the influence of different serial correlation assumptions on the power of N-of-1 clinical trials, as well as the robustness of inferences drawn when incorrect assumptions about the serial correlation are made, as considered in a recent set of simulation studies [9]. Second, we considered only fixed intervention periods with a pre-specified number of response collections over the course of a trial comparing two interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials that focus on intervention responses exhibited by individual patients have been described in the literature [3,4,5,6,7,8,9]. Such single subject or ‘N-of-1′ clinical trials have been conducted in a variety of ways, and although some recent studies have leveraged very sophisticated designs and clinical outcome measures [9,10,11], many N-of-1 studies pursued to date have lacked sophisticated experimental designs, data analysis methods, and inferential procedures [9,12]. In this context, Gabler et al [13] performed a systematic review of the literature for N-of-1 studies and found that of the 108 N-of-1 trials they identified from the literature involving a total of 2154 individuals, only 49% of those trials used statistical criteria to determine a superior intervention, whereas others used a graphical comparison (25%) or a clinical significance cutoff (20%).…”
Section: Introductionmentioning
confidence: 99%
“…However, in future work, it will be a further goal to also separate the dataset on the user level in a reasonable manner. That individual users play an important role in health care studies is emphasized by the emerging paradigm of N-of-1 studies [ 36 ].…”
Section: Methodsmentioning
confidence: 99%